Effect of vitamin E on follicular cell proliferation and expression of apoptosis-associated factors in rats with 6-N-propyl-2-thiouracil-induced goitrogenesis - Öner, J; Kükner, A; Öner, H; Ozan, E; Yekeler, H (Polish Histochemical Cytochemical Soc, 2003)
We have investigated immunohistochemically the effect of dl-alpha-tocopherol (vitamin E) on thyroid gland with 6-n-propyl-2-thiouracil (PTU)-induced hypothyroidism in rats. The animals were divided into four groups. Rats in group I were designated as control, rats in group 11 were treated with injections of PTU (10 mg/kg) for 15 days, rats in group III were treated with injections of PTU+vitamin E (10 mg/100g) for 15 days. Rats in group IV were treated with injections PTU for 15 days and kept for 15 next days after cessation of PTU treatment. At the end of experiment, the animals were killed by decapitation, blood samples were obtained, thyroid tissues were collected and processed for quantitative evaluation of immunohistochemical PCNA (marker of cell proliferation), Bax (pro-apoptotic marker) and Bcl-2 (anti-apoptotic marker) staining. There was an increase in the number of PCNA-immunopositive cells in follicular epithelial cells of group 11 rats compared with other groups (p<0.05). After vitamin E treatment, the number of PCNA-immunopositive cells decreased (p<0.05) while the number of Bax-immunopositive cells increased (p<0.05). The number of Bcl-2-positive follicular epithelial cells of group IV rats was higher than in those of other groups (p<0.05). The results of this study indicate that hypothyroidism induces cell proliferation in the thyroid gland and vitamin IS may promote involution of the gland.
Keywords: hypothyroidism; Bax; Bcl-2; PCNA; vitamin E; rat